Pengaruh Pemberian Biskuit Channa Striata Dan Tepung Kentang Terhadap Berat Badan Balita Wasted Di Puskesmas Makrayu Palembang - Kayla Assylla Saffa; Nurul Salasa Nilawati; Ahmad Sadiq (Media Gizi Kesmas, 2025)
Background: Wasting is a manifestation of chronic malnutrition, with low weight for height. The city of Palembang, especially the operational area of Makrayu Health Center, recorded second-highest prevalence of wasting in Palembang by 54 out of 4.396 toddlers experiencing wasting (1.22%). Local nutrition intervention, such as local food-based supplementary feeding, becomes a focal strategy to solve this problem. Objectives: The effect of biscuits made of snakehead fish and potato flour on the body weight in wasted toddlers was measured. Methods: This research is a quasi-experimental study with a one-group pretest-posttest design without a control group. The sample consisted of 33 toddlers aged 12-59 months who were wasting in the Makrayu Palembang Health Center work area. The intervention, in the form of providing snakehead fish biscuits and potato starch, was carried out for 14 days. Data were collected through body weight measurements before and after the intervention and assessment of nutrient intake using the 24-hour recall method. Data were analyzed using a dependent t-test. Results: Giving snakehead fish biscuits and potato starch showed a significant increase in body weight in wasting toddlers after the intervention, with an average increase of 0.32 kg. In addition, there was an increase in energy, protein, fat, and carbohydrate intake, which supported the improvement of nutritional status. Conclusion: There is an effect of giving snakehead fish biscuits and potato starch on the weight gain of wasting toddlers in the Makrayu Palembang Health Center work area (p=0.000).